Positivist, constructivist and critical approaches to international human resource management and some future directions. (May 2020) - Primecz, Henriett
International human resource management has become a mature discipline in the last 30 years. As a sub-discipline of social sciences, international human resource management is characterised by paradigmatic divisions. The aim of this review article is to map the presence of three dominant social science paradigms in the field. Four major journals which publish relevant studies of international human resource management have been analysed in order to give an overview of the paradigmatic state of play. After investigating 1649 articles, it is evident that positivist studies prevail, whereas constructivist works are in a minority. Critical approaches to international human resource management are largely absent in these journals. This paper presents examples of each type of research and explains the decisive characteristics of each paradigm. Finally, future directions are outlined: (1) more paradigm reflexivity is required, (2) non-mainstream (namely, constructivist and even critical) research is needed, and (3) new paradigmatic directions are recommended. Newly introduced paradigms or multiparadigm studies should be undertaken.